Assessment of furcation defects in hypertensive patients with chronic periodontitis - an institutional based retrospective study - R. SARAVANAN,; GANESH S, BALAJI (The journal of contemporary issues in business and government, 2020)
Periodontal disease is characterised by the loss of connective tissue attachment induced by the presence of putative periodontal pathogens within the gingival sulcus. The presence of furcation involvement is one clinical finding that can lead to a diagnosis of advanced and severe form of periodontitis and potentially to a less favorable prognosis for the affected teeth. The aim of the study is to assess the various types of furcation defects in hypertensive patients with chronic periodontitis. Among a sample of 42110 patients under the age group of 30 to 90 years in the Chennai population who visited a private dental college, a total of 858 patients who had met the inclusion criteria were selected for the study. Demographic details such as age and sex and grades of furcation involvement for all the patients were recorded. The required data was collected and analysed using SPSS(Statistical Package For The Social Sciences) Software. Chi-square test was used to study association between the parameters. The results were considered to be of statistical significance if p < 0.05. In the present study, there were more males (55.4%) than females (44.6%) in the study population and majority of patients were in the age group of 51-60 years of age (36.5%). Generalised chronic gingivitis (46.17%) was predominantly seen among the subjects followed by generalised chronic periodontitis (35.11%) and localised chronic periodontitis (18.72%). The association between the age groups and furcation in maxillary and mandibular posteriors, also association between the periodontal disease and furcation in maxillary and mandibular posteriors was evaluated, which was statistically significant.(p < 0.05) Within the limitations of the present retrospective analysis, it can be concluded that chronic periodontitis was more prevalent in hypertensive patients. There was lesser prevalence of furcation defects in maxillary and mandibular posteriors in hypertensive patients with chronic periodontitis. Additionally, grade 2 furcation of maxillary posteriors and grade 1 furcation of mandibular posteriors was most seen in the age group of 51-60 years.